Why do banks bear interest rate risk? - Christoph Memmel (Deutsche Bundesbank, 2017)
This paper investigates determinants of banks' structural exposure to interest rate risk in their banking book. Using bank-level data for German banks, we find evidence that a bank's exposure to interest rate risk depends on its presumed optimization horizon. The longer the presumed optimization horizon is, the more the bank is exposed to interest rate risk in its banking book. Moreover, there is evidence that banks hedge their earnings risk resulting from falling interest levels with exposure to interest rate risk. The more a bank is exposed to the risk of a decline in the interest rate level, the higher its exposure to interest rate risk.
Keywords: G21; 330; interest rate risk; banks' business model; hedging